Self-Control of Online Gambling Players on Legal Officials in Palembang: A Case Study - Sawi Sujarwo; Alif Abdullah (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
This study aims to determine the self-control of online gambling players on law enforcement officers in Palembang. Get detailed descriptions of the types of online gambling that have been played by law enforcement in Palembang. In this study, researchers used 2 research subjects and 4 people as sources of information. The results of this study found that the two subjects in this study each individual had achieved self-control not to play online gambling, it can be seen from the description of the factors that influence the subject's self-control. The two subjects were able to control themselves so they would not play online gambling again and not repeat the events that the two subjects had done. These results can be seen from the description of the factors that influence self-control which can be seen from the emerging themes.